2020
DOI: 10.18502/ijaai.v19i6.4932
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Serum Interleukins in Children with Idiopathic Nephrotic Syndrome

Abstract: Pro-inflammatory cytokines have been suggested in the pathogenesis of idiopathic nephrotic syndrome (INS), with conflicting results. This study was performed to identify alteration of different serum interleukins (ILs) in children with INS, and their predictive value in response to steroid treatment. Three groups of children (27; steroid-sensitive INS, 21; steroid-resistant INS, and 19 healthy controls) with normal serum C3, negative serologic tests of hepatitis B virus (HBV), hepatitis C virus (HCV), hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…In this study no correlation between Hpx and CRP was found, which does not exclude its hepatic synthesis by other inflammatory factors. Indeed, IL-6 levels have been shown to increase in MCD relapse, both in adults and children [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study no correlation between Hpx and CRP was found, which does not exclude its hepatic synthesis by other inflammatory factors. Indeed, IL-6 levels have been shown to increase in MCD relapse, both in adults and children [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…48 Therefore, a lower level of α-KG in SSNS patients may be linked with a high level of chronic inflammation in SSNS. 49 As α-KG like have a similar molecular, we suggested that α-KG like may have similar function as α-KG.…”
Section: Discussionmentioning
confidence: 73%
“…It is intriguing to discover that α‐KG promotes a longer, healthier life by reducing chronic inflammation 48 . Therefore, a lower level of α‐KG in SSNS patients may be linked with a high level of chronic inflammation in SSNS 49 . As α‐KG like have a similar molecular, we suggested that α‐KG like may have similar function as α‐KG.…”
Section: Discussionmentioning
confidence: 83%
“…Further, circulating pro-inflammatory cytokines from immune cells may be a third cause of injury to podocytes. Serum cytokines are increased in children with nephrotic syndrome as well as in Sh3bp2 KI/KI mice ( 11 , 12 , 55 59 , 70 ). Podocytes express receptors for TNF-α and IL-6, and we reported increased glomerular albumin permeability by TNF-α and IL-6 ( 71 , 72 ).…”
Section: Discussionmentioning
confidence: 99%